The Micropropagation of Bananas - A. Ernawati; , Rubbyanto; L. W. Gunawan; A. Purwito; D. Sukmana (Jurnal Agronomi Indonesia (Indonesian Journal of Agronomy), 2000)
A study to obtain a method of rapid clonal propagation of bananas was done. The investigated cultivars were Pisang Mas (AA), Pisang Ambon Kuning (AAA), Pisang Barangan (AAA), and Pisang Rajabulu (AAB). The basal medium was MS, the treatment were IAA (0 - 4.5 mg/l) and BAP (0 - 10.5m g/l), and the explants were suckers from the field. The experiment was designed with Randomized complete design, and repeated in 10 bottles for each treatment. The result of experiment showed that IAA alone significantly induced shoot multiplication. The role of IAA could be replaced by BAP. Cultivars, IAA and BAP interacted each other to induce shoot multiplication. The best treatment to induce shoot multiplication was the combination of IAA and BAP, and the concentration depend on the cultivar. After 8 weeks, the highest number of axilar shoots (12.6 shoots/bottles)w as obtained by Pisang Ambon (AAA), followed by Pisang Mas (AA) 8.2 shoot/bottle, Pisang Barangan (AAA) 7.8 shoot/bottle, and Pisang Rajabulu (AAB) 7.6 shoot/bottle.   Key words: Banana, Micropropagation